Psychological Analysis of the Main Characters in the Novel In the Land of Pepper by Ziggy Zezsyazeoviennazabrizkie: Analisis Psikologis Karakter Utama dalam Novel Di Negeri Lada Karya Ziggy Zezsyazeoviennazabrizkie - Noval Selpiansyah; Pepes Redi Juliansa; Irma Sendy Aristya (Universitas Muhammadiyah Sidoarjo, 2025)
Literature serves as a medium for expressing psychological realities, particularly through characters shaped by trauma and emotional struggle. Specifically, Ziggy Zezsyazeoviennazabrizkie’s In the Land of Pepper portrays the inner world of Salva, a child enduring neglect and domestic violence, whose psychological conflicts reflect broader societal issues. Despite existing studies on literary psychology, few have focused on Indonesian novels that depict childhood trauma using Freud's psychoanalytic theory. This study aims to analyze the protagonist’s psychological condition through Freud’s structural model—Id, Ego, and Superego—complemented by Jungian symbols and Eriksonian psychosocial theory. Results indicate Salva employs defense mechanisms such as denial, repression, and fantasy projection to navigate trauma, with the “land of pepper” functioning as a symbolic refuge. The novelty lies in the integrative psychoanalytic approach applied to a contemporary Indonesian text, highlighting the character’s fragmented psyche and imaginative resilience. Implications include the potential for literature to foster emotional literacy and trauma awareness in educational settings, as well as providing a foundation for further interdisciplinary research between literature and psychology.Highlight : The study analyzes the inner psychological struggles of the protagonist using Freud’s Id, Ego, and Superego. Childhood trauma and emotional neglect form the core of Salva’s development and coping mechanisms. Literature is presented as a medium for psychological reflection and emotional education through character exploration. Keywords : Literary Psychology, Main Character, Inner Conflict, Trauma, Ziggy Zezsyazeoviennazabrizkie